The ecological footprint new developments in policy and practice - Collins, Andrea; Flynn, Andrew; Edward Elgar Publishing (Cheltenham : Edward Elgar Pub. Ltd., 2015)
The ecological footprint is one of the most prominent tools used to measure environmental sustainability, and its rise in academic and policy debates since the early 1990s has been remarkable. Drawing upon research and examples from around the world, the authors critically examine the claims made of the Ecological Footprint and how it has been applied in practice. Offering an up-to-date account, this book provides a unique insight into the ways in which environmental knowledge is used within organisations, and how it is able to carry authority in policy making processes. It further discusses the changing status of the Ecological Footprint and the growth of other footprint tools, such as the Carbon Footprint. This book will be of interest to undergraduate and postgraduate students studying human geography, ecology, environmental science and urban studies. National and international policy makers concerned with developing sustainable strategies, measuring the environmental impact of key policy decisions and selecting indicators to measure progress towards sustainable development, will also find this to be a useful read.
1. Origins, diffusion and development of the ecological footprint -- 2. Government and the ecological footprint -- 3. Consumption and the city : the ecological footprint of Cardiff -- 4. Ecological footprinting in the United Kingdom -- 5. Novel applications, ecological footprint calculators and communication -- 6. Building a network for the ecological footprint community -- 7. Footprinting futures.
Includes bibliographical references and index.
Description based on online resource; title from title screen (viewed May 13, 2015).
Keywords: Sustainable development -- Measurement; Environmental impact analysis; Electronic books